Stormwater Infiltration in the Highway Environment: Guidance Manual - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
This report from earlier in 2020 is relevant to the latest issue of TR News (#328, on stormwater management).The infiltration approach to stormwater management involves the design, construction, and operation of engineered systems that infiltrate stormwater runoff into soils. These systems, referred to as “infiltration best management practices (BMPs),” are intended to reduce the volume of stormwater runoff and associated pollutants that discharge to stormwater systems and receiving waters via surface runoff.The TRB National Cooperative Highway Research Program's NCHRP Research Report 922: Stormwater Infiltration in the Highway Environment: Guidance Manual supports evaluation, selection, siting, design, and construction of infiltration BMPs in the highway environment. It is also intended to identify limitations on the use of infiltration and determine the need for alternative non-infiltration-based stormwater management approaches.Additional resources for the guide include:A Power Point presentation summarizing the projectAppendix A: Infiltration BMP Fact SheetsAppendix B: Infiltration Estimation Method Selection and Interpretation GuideAppendix C: Roadside BMP Groundwater Mounding Assessment Guide and User Tool (Excel-based tool)Appendix D: Guide for Assessing Potential Impacts of Highway Stormwater Infiltration on Water Balance and Groundwater Quality in Roadway Environments (Excel-based tool)Appendix E: Guide to Geotechnical Considerations Associated with Stormwater Infiltration Features in Urban Highway DesignAppendix F: BMP Clogging Risk Assessment Tool (Excel-based tool)Appendix G: Whole Lifecycle Cost and Performance ExampleAppendix H: Example Construction-Phase Checklists for Inspector and Contractor TrainingAppendix I: Summary of Infiltration Issues Related to Cold and Arid ClimatesAppendix J: BMP Case Study Reports
Keywords: Transportation and Infrastructure

Managing State Transportation Research Programs - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
TRB’s National Cooperative Highway Research Program (NCHRP) Synthesis 522: Managing State Transportation Research Programs identifies the current state of practice of managing state transportation research programs. The report highlights existing resources, desired individual skill sets, core competencies, and structures that are in place for departments of transportation (DOTs) to manage and conduct transportation research, especially federally funded research.In essence, NCHRP Synthesis 522 addresses how transportation agencies organize and manage their research programs to strive for quality and positive impacts on the transportation system over time (value). The report includes a four-dimensional framework to analyze and shed light on how state DOT research programs with differences in agency needs, resources, and constraints are able to produce programs of high quality and value.State transportation agencies conduct applied research with a goal of ultimately creating new knowledge to enhance the transportation system. Agency research as an activity requires special skills and capabilities—it convenes practitioners, scholars, and policy makers to identify and pursue the knowledge that is most needed.These and other attributes of research make it unlike other DOT functions such as planning, programming, construction, maintenance, and operations, even though it eventually enables agencies to perform those functions. The payoffs and innovative outcomes of research can be significant and valuable, although they are rarely immediate.
Keywords: Transportation and Infrastructure